Effects of adding bile acids to dietary storage japonica brown rice on growth performance, meat quality, and intestinal microbiota of growing–finishing Min pigs - Wang, Chuanqi; Zheng, Kexin; Wang, Dali; Yu, Hao; Zhao, Yun; Fang, Hengtong; Zhang, Jing (Frontiers in Veterinary Science, 2024)
This study investigated the effects of storage japonica brown rice (SJBR) and bile acids (BA) on the growth performance, meat quality, and intestinal microbiota of growing-finishing Min pigs. A total of 24 healthy Min pigs with a similar body weight of 42.25 ± 2.13 kg were randomly divided into three groups with eight replicates of 1 pig each. The groups were as follows: CON (50% corn), SJBR (25% corn + 25% SJBR), and SJBR+BA (25% corn + 25% SJBR + 0.025% hyodeoxycholic acid). The experimental period lasted from day 90 (the end of the nursery phase) to day 210 (the end of the finishing phase). The results showed the following: 1) Compared with the CON group, there was no significant difference in the average daily gain (ADG) and average daily feed intake (ADFI) of the SJBR and SJBR+BA groups, and the feed conversion ratio (FCR) was significantly decreased (P < 0.05). 2) Compared with the CON group, the total protein (TP) content in the serum was significantly increased, and the blood urea nitrogen (BUN) content was significantly decreased (P < 0.05) in the SJBR and SJBR+BA groups; moreover, HDL-C was significantly higher by 35% (P < 0.05) in the SJBR+BA group. 3) There were no significant differences in carcass weight, carcass length, pH, drip loss, cooking loss, and shear force among the groups; the eye muscle area was significantly increased in the SJBR group compared with the CON group (P < 0.05); back fat thickness was significantly decreased in the SJBR+BA compared with the SJBR (P < 0.05); and the addition of SJBR significantly increased the mRNA expression of MyHC-Ⅰ in the longissimus dorsi (LD) muscle of growing-finishing Min pigs (P < 0.05). 4) The cecal bacteria were detected using 16S rDNA, and the proportion of Lactobacillus was increased gradually at the genus level, but there was no significant difference among the different groups. In conclusion, 25% SJBR can improve the growth performance and increase the abundance of intestinal beneficial bacteria, and on this basis, adding bile acids can reduce the back fat thickness of growing-finishing Min pigs.